The relationship of social support to posttraumatic growth in COVID-19 among college students after experiencing campus lockdown: the effects of belief in a just world and meaning in life - Wu, Aoyu (Frontiers in Psychiatry, 2024)
Background Campus lockdown orders were issued for the purpose of preventing and controlling COVID-19, which resulted in psychological problems among college students. However, the experiences they have during the pandemic may also lead to positive personal changes, including posttraumatic growth (PTG). The current study examined the mediating role of belief in a just world and meaning in life in social support and PTG during the COVID-19 campus lockdown. Method An online survey was conducted on 1711 college students in Hebei Province, China. Based on the survey results, a structural equation model was established. Results Social support positively predicted PTG. Furthermore, belief in a just world and meaning in life played a mediating role between social support and PTG respectively. Besides, social support could also predict PTG through the multiple serial mediating effect of belief in a just world and meaning in life. Conclusions These results indicated mechanisms by which social support influenced PTG, and this provided insights into how to promote post-traumatic growth among university students in the post-pandemic period.